Indigenous in Jackie French’s Perspective as a White Author: Unsettling Narratives in Australian Children’s Book - Anandayu Suri Ardini (J-Lalite: Journal of English Studies, 2020)
How Australian children perceived the image of Indigenous from their readings is highly influenced by the authors. As many Australian children’s books are written by White authors, it is important to reveal whether their past and cultural background manifest in the image they built for Indigeneity. This study aims to reveal how Jackie French, a white Australian children’s book author, portrayed Indigenous characters and environment in her novels and to find out whether French creates a shift of the images as a form of her tendency to the major culture in Australia. The data were significant textual units from Nanberry Black Brother White novel and were analyzed using Bradford's post-colonial theory of unsettling narrative. The result of this study shows that French deliver a varying degree of Eurocentric mindset in portraying indigenous characters and characterization. It implies that French, as a White-Australian writer still possibly has a colonial mentality who, deliberately or not, positions the Indigenous characters as Others through the focalization of both Non-Indigenous and Indigenous characters themselves. For instance, in Nanberry Black Brother White, it appears that French try to justify whiteness as more civilized and a better race through Nanberry’s point of view as an Indigenous child character. It implies that the process of depicting Nanberry, the representation of Aborigines, in the novel is actually a justification for establishing an Eurocentric mindset through the character’s narratives, and therefore creates unsettling narratives.